Produksi Asam Asetat oleh Sel Acetobacter pasteurianus INT-7 Amobil pada Variasi Konsentrasi Etanol - Sri Luwihana; Endang Sri Rahayu; Slamet Sudarmadji; Kapti Rahayu (agriTECH, 2004)
Acetic acid fermentation by Acetobacter pasteurianus 1NT-7 immobilized cells with alginate gel on various ethanol concentration was investigated. Immobilized acetic acid bacteria cells were prepared with alginate gel 3% concentration with ratio cell suspension and alginat gel 1:3 (v/v) and conditioning time 24 hours. Fermentation using 10% immobilized cells (beads), medium of fermentation is YEPE (yeast extract pepton ethanol) with three ethanol concentration 5%, 7,5% and 10% respectively. Fermentation is going on shaker incubator with condition 100 rpm, 30" C for 10 days. The acetic acid production, pH and cells number were monitored for eveï€´y day. The immobilized cell fermentation was compared with free cells fermentation. The yield of free cells fermentation on 5% ethanol concentration is higher (84,6%) than immobilized cells yield (64,25 %), but on 7,5% and 10% ethanol concentration the immobilised cells yield is higher (62,77% and 45,44% respectively) than free cells yield ( 61,23% and 2,54% respectively).So the acetic acid fermentation using immobilized cells is effective on 7,5% ethanol concentration, while fermentation using free cells is effective on 5% ethanol concentration